Comportamiento productivo del ganado bovino de doble propósito de la zona sur-oeste de la provincia de Manabí. - Ganchozo Montesdeoca, Karen Vanessa (2017)
Bovine production is one of the most important items in the country. Therefore, the objective of this work was to determine the productive behavior of the cattle of dual purpose of the South-West zone of the province of Manabí. To this end, a question database related to the productive, health, social and economic areas of the Bolivar, Portoviejo and Rocafuerte areas was applied, with a sample of 210 surveys. The collection and management of information on livestock farms was of fundamental importance for the development of research. The data related to the tabulation of surveys were carried out in the program Microsoft Excel 2013, in which it was possible to perform a data management in an individualized way. In order to know the variables of daily milk production by area and total evaluated, the Fleischmann method was applied and values of dates of delivery, weaning, control and daily milk production were recorded. The graphs corresponding to the curves of milk production in lactation periods of January-August were made with free software. The results of the surveys revealed the current situation of most of the herds in the Manabí area, since their production has been deficient in recent years, mainly due to inconveniences of climatic origin, presence of diseases, and low price of milk and beef. The milk production curves recorded high values in the lactation periods, and decreased in the weaning stage (106 ± 21.3 kg) in all the analyzed areas.